Pembaharuan Islam dan Moderasi Beragama : Wasathiyah (Tazakka: Jurnal Pendidikan dan Keislaman, 2024)
The concept of Islamic Wasathiyah or Islamic moderation at this time has become a direction or flow of Islamic thought that has become a significant discourse in the Islamic world, seeing the reality of Muslims today who are always accused of separatist, anarchist and terrorist acts. Wasathiyyah means the best thing or a noble thing, meaning that the Islamic wasathiyyah teaching is the best teaching, because it follows the flow and development of the times by carrying out according to existing sharia law. The purpose: to know wasathiyah more deeply, to know the urgency faced by wasathiyah, to know the benefits of wasathiyah. The method used in this research is descriptive qualitative. This research is a  library research. Data sources were taken from books and articles that contain information about wasathiyah. The purpose of this research is to reveal the meaning of wasathiyah as a basic religious attitude that has a strong meaning and is stated in the Quranic verse about ummatan wasathan, the urgency of wasathiyah is Islamic moderation which means that all of its teachings have a sign of moderation because of this every Muslim is required to be moderate.
Keywords: Washatiyah; Moderation in Religion; Urgention of Wasathiyah